2023
DOI: 10.1111/hae.14836
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and cognitive factors involved in decision‐making process of haemophilia carriers in reproductive choices

Ilaria Cutica,
Mimosa Mortarino,
Isabella Garagiola
et al.

Abstract: IntroductionHaemophilia carriers (HCs) face a multitude of psychological challenges, mainly linked to the possibility of having an affected child. Important reproductive decisions such as opting for pre‐implantation genetic testing, or choosing prenatal diagnosis and then whether to continue or interrupt pregnancy in case of affected male fetus, have to be taken into consideration. Notwithstanding, the role of psychological characteristics on such decision‐making process needs further investigation.AimThe aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Women and girls with hemophilia, carriers and their partners must face important reproductive decisions, due to the possibility of having an affected child (41). Around 30% of women are unaware of their carrier status at the time of delivery, even if a positive family history is present (42, 43).…”
Section: Prenatal Diagnosis and Pre-implant Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Women and girls with hemophilia, carriers and their partners must face important reproductive decisions, due to the possibility of having an affected child (41). Around 30% of women are unaware of their carrier status at the time of delivery, even if a positive family history is present (42, 43).…”
Section: Prenatal Diagnosis and Pre-implant Evaluationmentioning
confidence: 99%
“…Studies investigating the experience of carriers throughout the reproductive decision-making and PND showed that the decisionmaking process depends on factors such as the severity of hemophilia of family members, their health-related quality of life, already having a child with hemophilia, living near a specialized medical center, having access to genetic and reproductive counseling and religious beliefs. Moreover, the cognitive and emotional aspects of this process are important as well (41,47).…”
Section: Prenatal Diagnosis and Pre-implant Evaluationmentioning
confidence: 99%